Handbuch Medien der Literatur - Binczek, Natalie; Dembeck, Till; Schäfer, Jörgen (DE GRUYTER, 2013)
There is a growing need for a survey presentation of the history and theory of media as they relate to literature. Thishandbook fills this gap and meets the need for a comprehensive survey of all media used for literary communication. It provides an inventory of the current state of research in this field, and will be an important source of basic information for both new and experienced students of literature, books, theater, film, the media, and cultural theory.